2006
DOI: 10.1248/cpb.54.452
|View full text |Cite
|
Sign up to set email alerts
|

Structural Scaffold of 18-Crown-6 Tetracarboxylic Acid for Optical Resolution of Chiral Amino Acid: X-Ray Crystal Analyses of Complexes of D- and L-Isomers of Serine and Glutamic Acid

Abstract: The separation of enantiomers is a subject of great interest, because the biologically effective chiral drug is either of enantiomers and the antipode is regarded as the impurity showing sometime high toxicity. Recently, the HPLC with chiral stationary phases (CSPs) has been extensively used to achieve the direct enantiomer separation. Crown ether, first introduced by Pedersen in 1967, 1,2) was shown by Cram et al. 3,4) to resolve enantiomers by the host-guest complexation. Since then, the optically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…2, (1) and (2)]. This conformation has also been observed in complexes of (1)-18C6H x with various optically active amino acids 19,20 and R-1-(1-naphthyl)-ethylamine. 26 Previously, we reported that the C 1 conformation of (1)-18C6H x could be further classified into three types, i.e.…”
Section: Conformation Of Crown Ether Ringsupporting
confidence: 57%
See 2 more Smart Citations
“…2, (1) and (2)]. This conformation has also been observed in complexes of (1)-18C6H x with various optically active amino acids 19,20 and R-1-(1-naphthyl)-ethylamine. 26 Previously, we reported that the C 1 conformation of (1)-18C6H x could be further classified into three types, i.e.…”
Section: Conformation Of Crown Ether Ringsupporting
confidence: 57%
“…Similar conformation has been observed in (1) Table 2). The short contacts 29 were observed for the Ca-HÁ Á ÁO, as shown in Figure 2 19,20 and are considered to be a major force for chiral separation of racemic amino acids.…”
Section: Conformation Of Crown Ether Ringmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with x-ray crystallography and nuclear magnetic resonance spectroscopy have demonstrated the affinity of 18c6H 4 for protonated amines, amino acids, amino alcohols and further compounds with free amino functionality. [8][9][10][11][12][13][14][15][16] Those studies have provided evidence for the relevance of the barrel-like and bowl-like structures adopted by 18c6H 4 . Such structures are sustained by intramolecular H-bonding involving the carboxyl groups and by intermolecular interactions of the cationic guest with the ether and carboxyl oxygen atoms.…”
Section: Introductionmentioning
confidence: 85%
“…Six multicomponent crystals of serine with organic counterparts containing carboxylic acid groups are known, namely l-serinium (+)-18-crown-6-tetracarboxylic acid perchlorate monohydrate and d-serinium (+)-tricarboxy-18-crown-6-carboxylate hexahydrate (Nagata et al, 2006), bis(dl-serinium) oxalate dihydrate (Alagar et al, 2002a), bis(l-serinium) oxalate dihydrate (forms I and II) (Braga et al, 2013), and a cocrystal of l-serine with pyridine-2,4-dicarboxylic acid (Liang, 2008). No anhydrous serinium salts or cocrystals of l and dl counterparts with the same chemical composition have been reported thus far.…”
Section: Commentmentioning
confidence: 99%